La colonne du Dôdékathéon à Délos - Pakkanen, Jari (Proceedings of the Danish Institute at Athens, 2000)
The temple ofTwelve Gods on Delos was most probably built in the beginning of third century BC. The column shaft reconstruction presented in this paper is based on the data published by E. Will (1955). The shaft had a slight entasis with a maximum projection of 5 mm approximately in the middle of the shaft. The closest parallels for the shaft profile may befound in fourth century BC Peloponnesian architecture and the third century BC Stoa in the sanctuary of Athena at Lindos. The column height of the Dodekatheon of 6.7 lower diameters is paralleled both in Late Classical and Early Hellenistic architecture.